(untitled) (Tikrit Journal For Political Science, 2023)
The study explores the intersection of "political Islam" and secularism, with a particular focus on Turkey as a model. Influenced by its historical legacy and cultural diversity, Turkey’s social and political landscape provides a compelling case study for understanding the complex dynamics between political Islam and secularism. This introduction highlights the importance of studying this topic, defines the problem of the study, summarizes the purpose of the study, describes the approach taken, and gives an overview of the structure of the study. The study adopts an interdisciplinary approach, incorporating elements from political science, history, sociology, and cultural studies. Uses qualitative study methods such as archival analysis, in-depth interviews, and literature review to collect and analyze data. By combining these approaches, the study seeks to provide a comprehensive understanding of the interaction between political Islam and secularism in Turkey. The study is divided into sections covering the concept of political Islam, the meaning of secularism, Turkey’s unique position between secularism and political Islam, and a synthesis of the main findings and ideas. Through its analysis, the study contributes to broader discussions about the compatibility of religious and secular ideologies in diverse societies, offering implications for both Turkey and other societies grappling with the challenges posed by political Islam and secularism.